Wiadomości . tygodnik NSZZ "Solidarność" Reg. Mazowsze, no. 263, 1987 ([s.n.], 1987)
Creation and circulation: Issue no. 2=52(1983) with imprint: for internal use, issue no. 3=53(1983) with caption: newsletter for internal use